The Effect of Market Organization on Competitive Equilibrium: the Multi-unit Case - Williams, Fred E. (Review of Economic Studies, 1973)
Journal Article The Effect of Market Organization on Competitive Equilibrium: the Multi-unit Case Get access Fred E. Williams Fred E. Williams Georgia Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 1, January 1973, Pages 97–113, https://doi.org/10.2307/2296742 Published: 01 January 1973